Euphorbia otjipembana subsp. okakoraensis (Euphorbiaceae), a new subspecies from the Kaokoveld, Namibia, with an amplified description of Euphorbia otjipembana - Swanepoel, Wessel (Phytotaxa, 2013)
Euphorbia otjipembana was hitherto only known from the type locality within the Kaokoveld Centre of Endemism, northwestern Namibia. Subsequently several additional populations were discovered, allowing for an amplified description of the species and the recognition of two subspecies. Euphorbia otjipembana subsp. okakoraensis, here described as a new subspecies, is only known from a small area within the Kaokoveld Centre. Diagnostic characters for subsp. okakoraensis include a shrubby habit and medium (up to 1 m) height, 5–7-angled, scarcely constricted branches with two pairs of spines per node and single cymes comprising of three horizontally arranged cyathia. A key as well as a comparative table with diagnostic morphological characters to distinguish between the two subspecies of E. otjipembana is provided.